De novo assembly and annotation of the Zhe-Maidong (Ophiopogon japonicus (L.f.) Ker-Gawl) transcriptome in different growth stages - Huijun Liu (Nature Portfolio, 2017)
Abstract Zhe-Maidong (Ophiopogon japonicus (L.f.) Ker-Gawl) is a traditional medicinal herb in the family Liliaceae that has significant pharmacological effects on immunity and cardiovascular disease. In this study, three different growth stages of Zhe-Maidong were investigated using RNA-seq, and a total of 16.4 Gb of raw data was obtained. After filtering and assembling, 96,738 unigenes with an average length of 605.3 bp were ultimately generated. A total of 77,300 unigenes were annotated using information from five databases, including the NT, NR, SwissProt, Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) databases. Additionally, the mechanisms of flavonoid, saponin and polysaccharide biosynthesis and of accumulation at different stages of tuber development were also characterized. From the first to third years, the contents of flavonoids, saponins and polysaccharides all increased, whereas the expression levels of related genes decreased in the flavonoid and saponin pathways and first increased and then decreased in the polysaccharide pathway. The results of this study provide the most comprehensive expressed sequence resource for Zhe-Maidong and will expand the available O. japonicus gene library and facilitate further genome-wide research and analyses of this species.